2018
DOI: 10.1111/tgis.12449
|View full text |Cite
|
Sign up to set email alerts
|

Creating a conceptual framework to improve the re‐usability of open geographic data in cities

Abstract: Open data has a profound effect on the working environment within which information is created and shared at all levels. At the local government level, open data initiatives have resulted in higher transparency in policy, a greater engagement between decisionmakers and citizens, and have changed the culture about how data analysis and evidence are used to support local governance. This article, based on data collected through an on-line survey, participatory workshops with data user communities in four cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(48 reference statements)
0
14
0
2
Order By: Relevance
“…Another critical aspect of the code to keep in mind is the type of licence attributed, which is also a notable metadata element. There is a general lack of knowledge about the meaning of each type of licence, which is one of the main barriers to reusing code (and data) [53]. As far as we develop open research, open licences for reuse should be adopted after evaluating the most appropriate choices [54].…”
Section: Collaborative Development and Code Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical aspect of the code to keep in mind is the type of licence attributed, which is also a notable metadata element. There is a general lack of knowledge about the meaning of each type of licence, which is one of the main barriers to reusing code (and data) [53]. As far as we develop open research, open licences for reuse should be adopted after evaluating the most appropriate choices [54].…”
Section: Collaborative Development and Code Sharingmentioning
confidence: 99%
“…In the proposed spectrum, we have included GIS standards as assets that should be taken into account when possible and, also based on several standards, "linked data" is used for publishing structured data so that they can be interlinked with other data, becoming more useful through semantic queries. This way, others can reuse the data to be applied in other scenarios or reproduce a previous experiment [53].…”
Section: Geospatial Data Availabilitymentioning
confidence: 99%
“…Some research has used Google Earth imagery to extract auxiliary information (Yang et al, ), taxation data (Jia & Gaughan, ; Kar & Hodgson, ), and social media data (Yu, Li, Zhu, & Plaza, ). New forms of data able to support spatial interpolation are available from three general sources as follows: Open data initiatives, from national mapping agencies, local government data portals (Benitez‐Paez, Comber, Trilles, & Huerta, ) to community‐led open data infrastructures such as the Open Data Institute ( https://theodi.org), and the many academic research led data centres, such as the CDRC ( https://www.cdrc.ac.uk) in the UK (Vij, ); Online service providers, particularly property sales and rentals for population interpolation, but also commercially produced but freely available Point‐Of‐Interest (POI) data; and Data generated by citizens through social media posts, check‐ins as well as citizen sensing and volunteered geographic information (VGI) activities such as OpenStreetMap, supported by mobile personal devices with web‐ and GPS‐enabled technologies. …”
Section: New Forms Of Datamentioning
confidence: 99%
“…Within GIScience, re-use of these datasets has attracted the interest from research, and previous work has suggested, inter alia, semantic application programming interfaces to retrieve datasets according to their thematic categories [16], a platform to monitor open data re-use [14], a one-stop portal for open data search [23], and a vision of intelligent geovisualization to exploit these datasets [15]. Direct and indirect costs of open geospatial data provision were discussed in [29]; Benitez-Paez et al [5] presented an empirically-derived taxonomy of barriers to open data re-use from a user's standpoint; and Benitez-Paez et al [4] proposed a conceptual framework to improve the reusability of open geographic data in cities.…”
Section: Introductionmentioning
confidence: 99%